Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1111/j.1471-0528.2007.01540.x
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor disorders 4 years after first delivery: a comparative study of restrictive versus systematic episiotomy

Abstract: Objective To compare two policies for episiotomy: restrictive and systematic.Design Quasi-randomised comparative study.Setting Two French university hospitals with contrasting policies for episiotomy: one using episiotomy restrictively and the second routinely.Population Seven hundred and seventy-four nulliparous women delivered during 1996 of a singleton in cephalic presentation at a term of 37-41 weeks.Methods A questionnaire was mailed 4 years after delivery. Sample size was calculated to allow us to show a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
16

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 17 publications
2
57
1
16
Order By: Relevance
“…A study conducted in the Midlands, with 2,100 participants, investigated the incidence of perineum morbidity in the postpartum showed that women who experienced perineum continuity of solution had greater representation for perineum morbidity than those who remained with perineum integrity (14) . The results of this study showed that routine usage of episiotomy does not seem to have protected the interviewees from suffering UI in the postpartum, these results were also found in a research conducted in France (10) .…”
Section: Discussionsupporting
confidence: 65%
“…A study conducted in the Midlands, with 2,100 participants, investigated the incidence of perineum morbidity in the postpartum showed that women who experienced perineum continuity of solution had greater representation for perineum morbidity than those who remained with perineum integrity (14) . The results of this study showed that routine usage of episiotomy does not seem to have protected the interviewees from suffering UI in the postpartum, these results were also found in a research conducted in France (10) .…”
Section: Discussionsupporting
confidence: 65%
“…Study by Fritel X reveals a policy of routine episiotomy does not protect against urinary or anal incontinence four years after first delivery. [9] Study by Chang shows episiotomy increased pain at weeks 1, 2 and 6 postpartum and urinary incontinence at 3 months postpartum. [12] The conclusion is after a prospective follow-up study of 243 women who completed the Taiwanese versions of the Short Form McGill Pain Questionnaire, International Consultation on Incontinence QuestionnaireUrinary Incontinence Short Form, Female Sexual Function Index and a demographic questionnaire after vaginal delivery in a Taiwanese Medical Center.…”
Section: Methodsmentioning
confidence: 99%
“…Another advantage of episiotomy that prevents pelvic organ prolapse also has been questioned. [9] Instead of preventing 3° and 4° perineal tear, episiotomy is responsible for 3° and 4° perineal tear. Traditionally, physicians have used episiotomies to minimize perineal trauma and postpartum pelvic floor dysfunction.…”
Section: Aim Of Studymentioning
confidence: 99%
“…The calculation is obtained by multiplying the frequency of the urine losses (1 = less than once a month; 2 = once or twice a month; 3 = one or several times a week; 4 = every day and/or night) by the amount of urine loss each time (1 = drops; 2 = small amount; 3 = large amount). According to the resulting index (1 to 12), incontinence is classified into mild (1 to 2), moderate (3 to 6), severe (8 to 9) or very severe (12).…”
Section: Methodsmentioning
confidence: 99%
“…The present study addressed UI in the postpartum period, as there is scarce national literature regarding this morbidity in this phase of the pregnancypuerperium cycle. In literature, studies state that urinary incontinence affect up to 74% of the formerly continent pregnant women (10)(11)(12) . Considering a population of age between 17 and 45 years, studies show UI prevalence in the postpartum between 20% and 27.5% (10,(12)(13)(14)(15) .…”
Section: Introductionmentioning
confidence: 99%